Fiscal Space for Health in Malawi and Revenue Potential of 'Innovative Financing' - World Bank Group (World Bank, Washington, DC, 2017)
Malawi’s population has grown rapidly from almost 3.6 million in 1960 to around 16.3 million in 2015 with about 85 percent of the population residing in rural areas. During the past twenty-five years, Malawi has made significant progress in increasing coverage for key maternal, child health and nutrition services, leading to improvements in several health outcomes. However, Significant health system bottlenecks limit service coverage and provision of quality health care. Gaps in service coverage and poor quality of service are symptomatic of a poorly financed and or inefficient health system. This report is organized as follows. The next section of this paper (Section 2) outlines the country context including the population and demographic characteristics, health service delivery, macro-fiscal situation, and the health financing profile. Section 3 presents the results from the fiscal space for health analysis for each of the five pillars namely: (i) Conducive macroeconomic environment; (ii) Re-prioritization for health; (iii) Generating additional resources for health; (iv) Increased health sector-specific foreign aid; and (v) Improved efficiency in the health sector. Section 4 provides the results from the review of the proposed areas for earmarked taxation while Section 5 summaries these results. Suffices to say that revenue forecasts on fuel and motor vehicle insurance are provided in the main body of the report while the analyses on extractives industry, alcohol, and tobacco products are provided in the Annexes. Lastly, Section 6 outlines the key conclusions and recommendations from the study.